Pemberdayaan Organisasi PKK dan UMKM Milik Bu Sri; Upaya Perbaikan Keterlibatan Wanita di Desa Setren - Shafira Rahmawati; Moy Yustiwa; Nadya Putri; Fairuz Sany; Nidya Arum; Hendra Maulana (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Women's empowerment is a modern concept that marks progressive changes in efforts to liberate from patriarchal culture, where women's involvement in society was previously very minimal. Efforts to align the portion of involvement of all genders are often referred to as the equal rights movement or women's liberation movement. In Setren Village, women's involvement is still low, with the achievement of SDG 5 point "Village Women's Involvement" only 26.32%. Based on this assessment, our community service work program is focused on increasing women's involvement. We initiated two main programs: empowerment of Village PKK Organizations through the creation of Village Gardens and education on Verticulture planting media, as well as rebranding of Mrs. Sri's Village MSMEs which operate in the soybean juice beverage sector. By partnering with the PKK, this women's empowerment organization is expected to be able to contribute to community development. Support for MSMEs also aims to improve the economic and environmental aspects of villages. This research aims to evaluate the results of the women's empowerment program in Setren Village. In contrast to previous research which focused on crafts, our approach uses planting media education and MSME support. The service will be carried out for three months, from March to July 2024, in accordance with the SDGs of Setren Village. The methods used include surveys, discussions and problem identification. Surveys were conducted at the Village Hall and the Village Head's house to obtain initial information. The second visit was made to Mrs. Sri's house to understand the condition of MSMEs. After identifying the problem, discussions were held to determine the work program based on the relevant Setren Village SDG point 5.